1997
DOI: 10.1097/00005768-199703000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Rat tendon morphologic and functional changes resulting from soft tissue mobilization

Abstract: Augmented Soft Tissue Mobilization (ASTM) is a new non-invasive soft tissue mobilization technique which has been used successfully to treat a variety of musculoskeletal disorders. The purpose of this study was to determine the effects of ASTM therapy on the morphological and functional characteristics of enzyme induced injured rat Achilles tendons. Four groups of five rats were allocated as follows: (A) control, (B) tendinitis, (C) tendinitis plus ASTM, and (D) ASTM alone. Collagenase injury was induced, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
186
1
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(197 citation statements)
references
References 15 publications
2
186
1
8
Order By: Relevance
“…20 ASTYM has been shown to cause increased fibroblast recruitment and activation in rat tendons which should theoretically promote proper healing, but this has not been thoroughly studied in humans. [21][22][23] ASTYM treatment is thought to activate a regenerative response in soft tissues via induction of leakage from dysfunctional capillaries which leads to fibroblast activation, macrophage mediated phagocytosis, and a local release of growth factors. [20][21][22][23][24] While eccentric exercise and ASTYM should theoretically be useful in the management of HHT, the research supporting both of these interventions is lacking and there are no studies that have reported the effects of a combined treatment approach.…”
Section: 13mentioning
confidence: 99%
“…20 ASTYM has been shown to cause increased fibroblast recruitment and activation in rat tendons which should theoretically promote proper healing, but this has not been thoroughly studied in humans. [21][22][23] ASTYM treatment is thought to activate a regenerative response in soft tissues via induction of leakage from dysfunctional capillaries which leads to fibroblast activation, macrophage mediated phagocytosis, and a local release of growth factors. [20][21][22][23][24] While eccentric exercise and ASTYM should theoretically be useful in the management of HHT, the research supporting both of these interventions is lacking and there are no studies that have reported the effects of a combined treatment approach.…”
Section: 13mentioning
confidence: 99%
“…32,33 At the cellular level, 32,33 the IASTM technique found to be effective in increasing blood flow, break up of soft tissue restrictions/ adhesions, tissue heating to the area, mast cell production and phagocytes, promote the restoration of normal tissue texture, enhance the proliferation of extracellular matrix fibroblasts, improve ion transport, decrease cell matrix adhesions, increase vascular response, and the remodeling of unorganized collagen fiber matrix following IASTM application which is much like the effect hypothesized in cross frictions by Cyriax (1984). 32,33 The application of the IASTM initiates the controlled microtrauma created by the instruments is hypothesised to create a localised inflammatory response, which allows for healing and scar tissue remodeling to take place. The remodeling of the collagen increases the elasticity of the scar tissue, breaks down fibrotic adhesions and increases functional capability or pliability of the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of pain reduction in the treatment of the IASTM may influence the larger fibers to close the "gate" and decrease the sensation of pain experienced. 32,33 The research that does exist regarding IASTM is largely made up of case studies and small-scale experiments. Burke et al evaluated the efficacy of IASTM on carpal tunnel syndrome and determined that it was in fact effective.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Perhaps, the initiation of this controlled microtrauma in an area of scar tissue or excessive fibrosis ultimately results in tissue remodeling through proper alignment of collagen fibers. 14,27,28 Additional studies have shown clinical efficacy using GT for the treatment of plantar fasciitis, tibialis posterior strain, carpal tunnel syndrome, lumbar compartment syndrome, and trigger thumb. 14,25,[29][30][31] Grade 5 high-velocity, low-amplitude manipulation was applied to the talocrural (ankle mortise) joint in an effort to alleviate perceived restriction of dorsiflexion movement as assessed by motion palpation.…”
Section: Discussionmentioning
confidence: 99%